Defining an Overdue Requiem for Palliative Cardiovascular Medicine. (September 2016) - Esselstyn, Caldwell B.
During the past 40 years, we have witnessed significant advances in the pharmaceutical and interventional treatment of cardiovascular disease (CVD), which have helped achieve a decrease in morbidity and mortality for this illness. Nevertheless, CVD remains the number 1 killer of women and men in Western civilizations. This fact is in stark contrast to the scenario in multiple whole food, plant-based nutrition (WFPBN) cultures, where CVD is virtually nonexistent. The utility of plant-based nutrition to halt and prevent CVD has been demonstrated epidemiologically, during wartime deprivation, in large cohort and population transitioning studies, and through prospective randomized and nonrandomized investigations. A basic scientific study confirms that omnivores have intestinal bacteria capable of converting animal food to trimethylamine oxide (TMAO), which injures blood vessels, whereas those eating plants only do not have intestinal bacteria capable of producing TMAO. Despite this overwhelming evidence for the safety, simplicity, and efficacy of plant nutrition to halt and prevent coronary artery disease, the cardiovascular medicine community has failed to embrace this option of therapy and persists in palliative treatments associated with high morbidity, mortality, and expense. It is long overdue to question why.